1996
DOI: 10.1172/jci119045
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil recruitment to the lung in a murine model of allergic inflammation. The role of T cells, chemokines, and adhesion receptors.

Abstract: Eosinophil accumulation is a distinctive feature of lung allergic inflammation. Here, we have used a mouse model of OVA (ovalbumin)-induced pulmonary eosinophilia to study the cellular and molecular mechanisms for this selective recruitment of eosinophils to the airways. In this model there was an early accumulation of infiltrating monocytes/macrophages in the lung during the OVA treatment, whereas the increase in infiltrating T-lymphocytes paralleled the accumulation of eosinophils. The kinetics of accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
302
2
7

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(336 citation statements)
references
References 81 publications
25
302
2
7
Order By: Relevance
“…The CC and CXC chemokine groups are large and contain over 50 identified ligands. Although in vitro characterizations would suggest that there is impressive redundancy in this system, examinations of a limited number of ligands in vivo have demonstrated that their production is organized in a coordinated manner and that their effector functions can be restricted to different stages of disease development and/or pathology (17,18,39,44). Thus, in vivo, a deficiency of an individual ligand or its receptor can cause striking alterations in tissue phenotype (16,19).…”
Section: Figurementioning
confidence: 99%
“…The CC and CXC chemokine groups are large and contain over 50 identified ligands. Although in vitro characterizations would suggest that there is impressive redundancy in this system, examinations of a limited number of ligands in vivo have demonstrated that their production is organized in a coordinated manner and that their effector functions can be restricted to different stages of disease development and/or pathology (17,18,39,44). Thus, in vivo, a deficiency of an individual ligand or its receptor can cause striking alterations in tissue phenotype (16,19).…”
Section: Figurementioning
confidence: 99%
“…[5][6][7][8][9][10] However, these responses have typically been assessed in isolation from each other. We have recently demonstrated that C57BL/6J mice undergo a biphasic response to aerosolized ovalbumin (OVA) exposure.…”
mentioning
confidence: 99%
“…Th17 cells, which differentiate from naïve CD4+ T cells under the influence of IL-6/IL-21/IL-23 and transforming growth factor (TGF)-via the signal transducer and activator of transcription 3 (STAT3)-ROR t pathway, are mainly responsible for neutrophilia in allergic severe asthma (Louten et al 2009 Conversely, investigations into the contribution of cytotoxic CD8+ T cells towards the development of allergic airway inflammation are not well understood. The depletion of CD8+ T cells does not affect airway response to allergen challenge in mice (Gonzalo et al 1996). However, a subset of CD8+ T cells, named Tc2 cells, can produce Th2 cytokines such as IL-4, IL-5, and IL-13, which are increased in the bronchoalveolar lavage fluids (BALF) of allergic asthmatic patients in studies.…”
Section: Role Of T Cells In Airways Allergy Diseasementioning
confidence: 99%